“Meup Onle Ate, Tah Onle Usif”: Lensa Filosofis Memahami Orang Dawan Dan Dunia Kerjanya - Raioan , Agrindo Zandro (Aditya Wacana Pusat Pengkajian Agama Dan Kebudayaan, 2022)
This article describes the human profile of the Dawanese in two dimensions, namely anthropological and ecological. This two-dimensional description leads to an essence called the ‘world of work’. These two dimensions are seen in the cultural philosophy lens in the form of the Dawan people’s philosophy of life in the world of work. For the Dawanese, work is an essential element of their existence. By working, Dawan humans can realize who he is and can also express his relationship with the natural surroundings. The methodology in this article is a phenomenological philosophical study combined with a literature study. This article finds that for the Dawanese, work is not only to find food, but first of all as a form of embodiment of true self-identity and a moment where Dawanese can relate and unite with nature. The tipycal contribution of this paper is all humans, especially Dawanese, must to have the will of working. Not only for eating and drinking, more than that, working must be in a harmony with a holistic self-realization and a time when humans can unite and relate to the natural surroundings